Synthesis of MA-AM-MMA Copolymer and its Inhibition Performance Against Calcium Phosphate Scale - He, Aijiang; Liu, Lixiu; Li, Xiangbiao; Yu, Huiling (Asian Journal of Chemistry, 2013)
A multifunctional ternary copolymer was synthesized from maleic anhydride (MA), acrylamide (AM) and methyl methacrylate (MMA). The effects of the reaction temperature, polymerization time, amount of initiator and monomer ratio on the inhibition performance of the copolymer against calcium phosphate scale were determined. The optimum conditions for synthesis are as follows: reaction temperature, 75 ºC; polymerization time, 4 h; amount of initiator, 15 % and monomer molar ratio of MA:AM:MMA, 3:2:1. A scale inhibition efficiency of over 90 % was obtained with the dosage of 25 mg/L of the copolymer and the transmittance of dispersed ferric oxide was less than 30 % with the concentration of 10 mg/L copolymer, which enabled good performance in scale-formation inhibition and dispersion. Infrared spectroscopy results suggested the presence of functional groups, including carboxyl, ester and amide groups, in the terpolymer.